A lignin xanthate zinc vulcanization accelerator and its preparation method and application
By using the use of lignin oligate zinc hyaccharide complexes in rubber vulcanization, the health and environmental risk problems of rubber sulfurization promoters in existing technologies have been solved, and high -efficiency and multi -functional vulcanization effects are achieved, and the rubber materials are improved Performance.
Patent Information
- Application Number
- CN202410365138.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-03-28
AI Technical Summary
Existing rubber vulcanization accelerators have potential human health and environmental risks, and vulcanization promotion performance is low and has a single function, making it difficult to meet the needs of environmental protection and performance improvement.
The use of lignarin zinc sulfate vulcanized promoters, reacts with hydroxytic lignin and carbonide, and adds zinc -containing compound flocculation to prepare a zinc load load in a complex in the three -dimensional mesh structure of lignin to improve the decentralization of zinc The vulcanization efficiency of rubber material.
Significantly accelerate the vulcanization speed, improve the sulfurization efficiency, reduce single consumption, enhance the tensile strength and mechanical properties of rubber materials, while reducing the amount of zinc use and reducing environmental pollution.
Smart Images

Figure QLYQS_1 
Figure BDA0004763990110000021 
Figure HDA0004763990120000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of rubber technology, and in particular to a lignin zinc xanthate vulcanization accelerator and a preparation method and application thereof. Background Art
[0002] Lignin is an aromatic natural polymer with a three-dimensional network structure extracted from plant cell walls. Its chemical structure is composed of guaiacyl, syringyl and p-hydroxyphenyl. The bonding mode of these three units is mainly ether bonds. In the paper and cellulose industry, the annual global production of lignin is 150 million tons, of which only 2% is used for lignin-derived products. The rest of the lignin is usually used as fuel by burning, and its value is not fully utilized. Due to the advantages of lignin's rich aromatic structure, low density, renewability, antioxidant and biodegradability, it has become an ideal material for the development of composite materials. It can not only reduce the production cost of enterprises and reduce environmental pollution, but also conform to the development trend of high performance, multifunctionality and greenness of new materials in my country. It is of great significance in promoting the ecological utilization of renewable resources and alleviating the shortage of petrochemical resources.
[0003] In order to adapt to the increasingly stringent environmental protection requirements, the green development of rubber additives in the rubber industry has become a general trend in recent years. Zinc oxide with special physical and chemical properties is often used as a rubber vulcanization activator and plays an important role in the vulcanization and use of rubber products, such as increasing crosslinking density, improving vulcanization efficiency and improving the heat resistance of rubber products. Zinc ions and their organic complexes released by rubber products containing zinc oxide during use and storage will harm aquatic organisms, destroy aquatic ecosystems, and may harm human health. Therefore, it is urgent to reduce the amount of zinc oxide in various rubber formulas to reduce the environmental pollution caused by zinc ions and their organic complexes.
[0004] At present, rubber vulcanization accelerators generally have potential human health and environmental risk problems, and the vulcanization accelerator efficiency is low and the function is single. Therefore, the development of non-toxic, no or less zinc oxide, efficient and multifunctional new vulcanization accelerators is of great significance to the rubber industry. For example, Chinese invention CN113929608 A discloses a method for preparing a vulcanization accelerator, comprising the following steps: adding carbon disulfide to a mixed aqueous solution of selenium oxide and glutamic acid, and reacting to obtain a vulcanization accelerator, but the cost is high and the vulcanization efficiency is not high, which still needs to be improved. For example, nano zinc oxide replaces traditional zinc oxide, organic zinc complex replaces zinc oxide, nano inorganic filler zinc loading technology, and develops other divalent metal oxide activators and rare earth multifunctional rubber vulcanizers. Since zinc ions really play an activating role in the vulcanization process, the traditional zinc oxide activated vulcanization reaction is essentially an interfacial reaction, and only the zinc ions on the surface of zinc oxide can play a role, and a large amount of internal zinc ions are still bound in the zinc oxide lattice, so that most of the zinc oxide cannot be fully utilized, which will cause great waste. Therefore, the present invention provides a lignin zinc xanthate vulcanization accelerator and a preparation method and application thereof. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a lignin xanthate zinc vulcanization accelerator and its preparation method and application in view of the deficiencies in the prior art.
[0006] In order to solve the above technical problems, the present invention discloses the following technical solutions:
[0007] In a first aspect, the present invention discloses a lignin xanthate zinc vulcanization accelerator as shown in Formula I, wherein the vulcanization accelerator contains an ultra-fast vulcanization accelerator xanthate; S and Zn are bound by metal chelation;
[0008]
[0009] In a second aspect, the present invention discloses a method for preparing the lignin zinc xanthate vulcanization accelerator described in the first aspect, comprising: reacting hydroxymethylated lignin with carbon disulfide, and then adding a zinc-containing compound for flocculation, and the resulting precipitate is the lignin zinc xanthate vulcanization accelerator.
[0010] The preparation method of hydroxymethylated lignin comprises adding aldehyde compounds to a liquid containing lignin substances for reaction, preferably heating the liquid containing lignin substances to 65-75°C, and adding aldehyde compounds for reaction. The liquid containing lignin substances is a liquid containing one or more of lignin, lignin sulfonate or lignin derivatives; in the preparation method of hydroxymethylated lignin, the pH of the liquid containing lignin substances is 10-14, preferably 11-13; the concentration of lignin substances in the liquid containing lignin substances is 35-45 mg / mL; the aldehyde compounds include formaldehyde; the mass ratio of the lignin substances to the aldehyde compounds is 5-7:1, preferably 6:1; the reaction temperature is 65-75°C, the reaction time is 3.5-4.5h; the reaction is carried out under stirring; the stirring rate is 200-400rpm.
[0011] Wherein, the mass ratio of the hydroxymethylated lignin to carbon disulfide is 1:0.5-1.5, preferably 1:1.
[0012] Wherein, the zinc-containing compound is any one or more combinations of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate; the zinc-containing compound is added in the form of a zinc-containing compound solution, and the mass fraction of the zinc-containing compound solution is 10%-15%, preferably 10%; the molar volume ratio of the hydroxymethylated lignin to the zinc-containing compound solution is 1 mol:6.3-10.3L, preferably 1 mol:7.3-9.3L.
[0013] Wherein, the reaction temperature is 35-45°C, and the reaction time is 3.5-4.5h.
[0014] In a third aspect, the present invention discloses the use of the lignin xanthate zinc vulcanization accelerator described in the first aspect or the lignin xanthate zinc vulcanization accelerator prepared by the method described in the second aspect in the preparation of rubber materials.
[0015] Wherein, the weight of the lignin zinc xanthate vulcanization accelerator is 5-10 parts per 100 parts of styrene-butadiene latex.
[0016] Wherein, the rubber material is made of the following components in parts by weight: 100 parts of styrene butadiene latex, 40-50 parts of carbon black, 5-10 parts of lignin xanthate zinc vulcanization accelerator, 1-3 parts of stearic acid, 3-5 parts of zinc oxide, and 2-3 parts of vulcanizing agent; preferably, the solid content of the styrene butadiene latex is 15%-25%, preferably 20%.
[0017] Wherein, the preparation method of the rubber material comprises:
[0018] (1) dissolving a lignin xanthate zinc vulcanization accelerator in an alkali solution, mixing the mixture with styrene-butadiene latex, flocculating under acidic conditions, washing, and drying to obtain a co-precipitated rubber;
[0019] (2) mixing the obtained co-precipitated rubber with other auxiliary materials;
[0020] (3) Finally, the obtained mixed rubber is vulcanized and molded to obtain the rubber material.
[0021] In step (1), the alkali solution is a sodium hydroxide solution with a pH value of 10 to 12.
[0022] In step (2), the obtained coprecipitated rubber is mixed with stearic acid, zinc oxide and carbon black, and the obtained mixed rubber is mixed with a vulcanizing agent.
[0023] Step (3) vulcanizing the obtained mixed rubber at 151° C. to obtain the rubber material.
[0024] In summary, the present invention provides a lignin zinc salt complex, which increases the dispersibility of zinc in the rubber matrix by loading zinc in the three-dimensional network structure of lignin, avoids zinc agglomeration, and also improves the dispersibility of lignin in the rubber matrix.
[0025] Beneficial effects:
[0026] The present invention uses lignin as a raw material, which is cheap, readily available, renewable, can effectively save resources, protect the environment, and realize the high-value utilization of lignin.
[0027] The vulcanization accelerator of the present invention is a xanthate accelerator, which can cooperate with other vulcanization aids to significantly accelerate the vulcanization speed, improve the vulcanization efficiency, reduce the unit consumption, and increase the crosslinking density, thereby improving the tensile strength of the rubber material.
[0028] The vulcanization accelerator of the present invention can shield the hydroxyl groups and other polar groups on the surface of lignin, effectively improving the dispersibility of lignin in rubber. At the same time, since lignin has a three-dimensional network structure, zinc is loaded on its network structure, the dispersibility of zinc is also improved, and the agglomeration of zinc is avoided, so that the use amount of zinc can be reduced and zinc pollution can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0030] Figure 1 The infrared spectra of the original lignin (L) and the prepared lignin zinc xanthate (QL-S) vulcanization accelerator. DETAILED DESCRIPTION
[0031] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0032] The concentration of the formaldehyde solution described in the following examples is 38%.
[0033] In the following examples, the zinc sulfate solution and the zinc acetate solution are both aqueous solutions with a mass fraction of 10%.
[0034] In the following examples, the molecular weight of the industrial lignin is 2276 g / mol, and the molar weight of 20 g of industrial lignin is 0.0088 mol.
[0035] Embodiment 1:
[0036] (1) Add 20 g of industrial lignin to 480 ml of pure water, add an appropriate amount of NaOH to adjust the solution pH to 12 and stir until dissolved, pour the lignin alkaline solution into a three-necked flask and stir, heat to 70 ° C and slowly add formaldehyde solution to start the reaction, the reaction speed is 300 r / min, the reaction time is 4 h (the mass ratio of lignin to formaldehyde is 6:1), and a reaction solution containing hydroxymethylated lignin is obtained.
[0037] (2) The reaction solution containing hydroxymethylated lignin obtained in step (1) is cooled to 40°C and slowly CS2 is added, the reaction speed is 300r / min, and the reaction time is 4h. Stirring is continued, and 50ml of 10% by mass zinc sulfate solution is added for flocculation, filtered, the filter cake is washed with water, dried (the drying temperature of the blast dryer is 60°C, the time is 24h), and air flow pulverized to obtain a lignin xanthate zinc vulcanization accelerator with a particle size of 2-3μm (the mass ratio of industrial lignin to CS2 is 1:1).
[0038] (3) Disperse 5 parts (2 g) of lignin zinc xanthate vulcanization accelerator in 20% solid content styrene-butadiene latex (100 parts) and mix at 700 rpm for 10 min. Then adjust the mixed solution to pH 4 with 1 mol / L dilute hydrochloric acid to allow it to flocculate fully. Filter and wash with water until the filtrate has a pH of more than 6. Dry it in a forced air oven at 60°C to obtain a co-precipitated rubber.
[0039] (4) Add 105 parts of the coprecipitated rubber for internal mixing, then accurately weigh 1 part of stearic acid, 3 parts of zinc oxide, and 40 parts of carbon black, add them to an internal mixer in sequence, and mix at 60°C for 8 minutes.
[0040] (5) The rubber mixture obtained in step (4) is added to the roll of an open mixing mill, 2 parts of sulfur is added, and mixed at 20° C. for 6 minutes, and then thinned and triangularly packaged.
[0041] (6) vulcanizing the rubber mixture obtained in step (5) at 151° C. to obtain the rubber material.
[0042] pass Figure 1 Infrared spectra of the original lignin (L) and the prepared lignin xanthate zinc (QL-S) vulcanization accelerator at 750 cm -1 、690cm -1 Two new peaks appeared, which were the stretching vibrations of C=S and CS bonds, indicating that the grafting was successful.
[0043] Embodiment 2:
[0044] 1) Add 20g of industrial lignin to 480ml of pure water, add appropriate amount of NaOH to adjust the solution pH to 12 and stir until dissolved, pour the lignin alkaline solution into a three-necked flask and stir, heat to 70°C and slowly add formaldehyde solution to start the reaction, the reaction speed is 300r / min, the reaction time is 4h (the mass ratio of lignin to formaldehyde is 6:1), and obtain a reaction solution containing hydroxymethylated lignin.
[0045] (2) The reaction solution containing hydroxymethylated lignin obtained in step (1) is cooled to 40°C and slowly added with CS2, the reaction speed is 300r / min, and the reaction time is 4h. Continue stirring, pour into a beaker and flocculate with 10% by mass zinc sulfate, filter, wash the filter cake with water, dry (the drying temperature of the blast dryer is 60°C, the time is 24h), and air flow pulverize to obtain a lignin xanthate zinc vulcanization accelerator with a particle size of 2-3μm (the mass ratio of industrial lignin to CS2 is 1:1).
[0046] (3) Disperse 10 parts (4 g) of lignin zinc xanthate vulcanization accelerator in 20% solid content of styrene-butadiene latex and mix at 700 rpm for 10 min. Then adjust the pH of the mixture to 4 with 1 mol / L dilute hydrochloric acid to fully flocculate it. Filter and wash with water until the pH of the filtrate is above 6. Dry it in a forced air oven at 60°C to obtain a co-precipitated rubber.
[0047] (4) Add 110 parts of coprecipitated rubber for internal mixing, then accurately weigh 1 part of stearic acid, 3 parts of zinc oxide, and 40 parts of carbon black, add them to the internal mixer in sequence, and mix at 60°C for 8 minutes.
[0048] (5) The rubber mixture obtained in step (4) is added to the roll of an open mixing mill, 2 parts of sulfur is added, and mixed at 20° C. for 6 minutes, and then thinned and triangularly packaged.
[0049] (6) vulcanizing the rubber mixture obtained in step (5) at 151° C. to obtain the rubber material.
[0050] Embodiment 3:
[0051] (1) Add 20 g of industrial lignin to 480 ml of pure water, add an appropriate amount of NaOH to adjust the solution pH to 12 and stir until dissolved, pour the lignin alkaline solution into a three-necked flask and stir, heat to 70 ° C and slowly add formaldehyde solution to start the reaction, the reaction speed is 300 r / min, the reaction time is 4 h (the mass ratio of lignin to formaldehyde is 6:1), and a reaction solution containing hydroxymethylated lignin is obtained.
[0052] (2) The reaction solution containing hydroxymethylated lignin obtained in step (1) is cooled to 40°C and slowly added with CS2, the reaction speed is 300r / min, and the reaction time is 4h. Continue stirring, pour into a beaker and flocculate with 10% zinc acetate by mass, filter, wash the filter cake with water, dry (the drying temperature of the blast dryer is 60°C, the time is 24h), and air flow pulverize to obtain a lignin xanthate zinc vulcanization accelerator with a particle size of 2-3μm (the mass ratio of industrial lignin to CS2 is 1:1).
[0053] (3) Disperse 5 parts (2 g) of lignin zinc xanthate vulcanization accelerator in 20% solid content of styrene-butadiene latex and mix at 700 rpm for 10 min. Then adjust the mixed solution to pH 4 with 1 mol / L dilute hydrochloric acid to allow it to flocculate fully. Filter and wash with water until the filtrate has a pH of more than 6. Dry it in a forced air oven at 60°C to obtain a co-precipitated rubber.
[0054] (4) Add 105 parts of the coprecipitated rubber for internal mixing, then accurately weigh 1 part of stearic acid, 3 parts of zinc oxide, and 40 parts of carbon black, add them to an internal mixer in sequence, and mix at 60°C for 8 minutes.
[0055] (5) The rubber mixture obtained in step (4) is added to the roll of an open mixing mill, 2 parts of sulfur is added, and mixed at 20° C. for 6 minutes, and then thinned and triangularly packaged.
[0056] (6) vulcanizing the rubber mixture obtained in step (5) at 151° C. to obtain the rubber material.
[0057] Comparative Example 1: Unmodified industrial lignin
[0058] (1) Dissolve 5 parts (2 g) of unmodified industrial lignin in a sodium hydroxide solution at pH = 11; after complete dissolution, mix it with styrene-butadiene latex having a solid content of 20% and mix at 700 rpm for 10 min, then adjust the mixed solution to pH = 4 with 1 mol / L dilute hydrochloric acid to fully flocculate it, filter it, wash it with water until the pH of the filtrate is above 6, and dry it in a forced air oven at 60°C to obtain a co-precipitated glue.
[0059] (2) Add 105 parts of coprecipitated rubber for internal mixing, then accurately weigh 1 part of stearic acid, 3 parts of zinc oxide, and 40 parts of carbon black, add them to an internal mixer in sequence, and mix at 60°C for 8 minutes.
[0060] (3) Add the mixed rubber obtained in step (2) to the roll of the open mill, add 2 parts of sulfur and mix at 20°C for 6 minutes, and then thin and triangle wrap it.
[0061] (4) vulcanizing the rubber mixture obtained in step (3) at 151° C. to obtain the rubber material.
[0062] Comparative Example 2: No vulcanization accelerator added
[0063] (1) A styrene-butadiene latex having a solid content of 20% was stirred at a rotation speed of 700 rpm for 10 min, and then the mixed solution was adjusted to pH = 4 with 1 mol / L dilute hydrochloric acid to fully flocculate, filtered, washed with water until the pH of the filtrate was above 6, and dried in a blast oven at 60° C. to obtain styrene-butadiene rubber.
[0064] (2) 105 parts of styrene-butadiene rubber were added for internal mixing, and then 1 part of stearic acid, 3 parts of zinc oxide and 40 parts of carbon black were accurately weighed and added to an internal mixer in sequence, and then internal mixing was performed at 60° C. for 8 minutes.
[0065] (3) The rubber mixture obtained in step (2) is added to the roll of an open mixing mill, 2 parts of sulfur is added, and mixed at 20° C. for 6 minutes, and then thinned and triangularly packaged.
[0066] (4) vulcanizing the rubber mixture obtained in step (3) at 151° C. to obtain the rubber material.
[0067] Comparative Example 3: Replace the vulcanization accelerator with accelerator DM (i.e. 2,2'-dibenzothiazole disulfide)
[0068] (1) A styrene-butadiene latex having a solid content of 20% was stirred at a rotation speed of 700 rpm for 10 min, and then the mixed solution was adjusted to pH = 4 with 1 mol / L dilute hydrochloric acid to fully flocculate, filtered, washed with water until the pH of the filtrate was above 6, and dried in a blast oven at 60° C. to obtain styrene-butadiene rubber.
[0069] (2) Add 100 parts of styrene-butadiene rubber for internal mixing, then accurately weigh 1 part of stearic acid, 3 parts of zinc oxide, and 40 parts of carbon black, add them to an internal mixer in sequence, and mix them at 60°C for 8 minutes.
[0070] (3) Add the rubber mixture obtained in step (2) to the roll of the open mill, add 2 parts of sulfur and 2 parts of vulcanization accelerator DM, mix at 20° C. for 6 min, and thin-pass and triangle-package.
[0071] (4) vulcanizing the rubber mixture obtained in step (3) at 151° C. to obtain the rubber material.
[0072] The above embodiments and comparative examples are tested:
[0073] (1) Elemental analysis tests were performed on the original lignin and the prepared vulcanization accelerator.
[0074] (2) Vulcanization characteristics test, tested by a rotorless vulcanizer.
[0075] (3) Mechanical properties test, the test content and methods are as follows:
[0076] Performance of vulcanized rubber - vulcanization characteristics: test method see GB / T 16584-1996;
[0077] Tensile strength: test method see GB / T 528-2009;
[0078] Elongation at break: test method see GB / T 528-2009;
[0079] Tensile stress: test method see GB / T 528-2009;
[0080] Tested by electronic universal testing machine.
[0081] (4) Oxidation induction time test: The prepared rubber material is tested by a differential calorimeter. The test method is shown in GB / T 19466.6-2009.
[0082] The experimental results are as follows:
[0083] 1. Elemental analysis
[0084] Table 1 Elemental analysis of the vulcanization accelerators prepared in Examples 2-4 and the original lignin
[0085] name C(%) H(%) N(%) S(%) Original lignin 62.38 5.58 0.26 0.23 Example 2 56.19 5.34 0.24 8.34 Example 3 56.35 5.47 0.25 8.21
[0086] As can be seen from Table 1, the S content of the original lignin was measured to be 0.23%, while the S content of the modified lignin zinc xanthate vulcanization accelerator was significantly increased, reaching 35.70-36.26 times that of the original lignin. This result shows that the lignin was successfully grafted with the -CS2- group.
[0087] 2. Rubber vulcanization characteristics
[0088] As can be seen from Table 2, compared with Comparative Example 3, the vulcanization rate and torque of Examples 1-3 are significantly improved compared with Comparative Example 3, and the effect is more obvious with the increase of the number of lignin zinc dithiocarbamate vulcanization accelerators; compared with Comparative Example 1, the Tc90 of the unmodified lignin is extended in Example 1, that is, the unmodified lignin delays the vulcanization rate. The vulcanization efficiency of the present invention is also improved compared with the traditional vulcanization accelerator (DM).
[0089] Table 2 Rubber vulcanization characteristics of Examples 1-3 and Comparative Examples 1-3
[0090] MH (dN·m) ML (dN·m) Tc10(min) Tc90(min) Example 1 16.21 1.35 1.63 9.34 Example 2 18.14 1.39 1.86 6.22 Example 3 16.02 1.28 1.59 10.11 Comparative Example 1 11.41 1.24 1.74 22.42 Comparative Example 2 12.26 1.25 1.24 21.61 Comparative Example 3 15.52 1.34 1.52 16.14
[0091] 3. Mechanical properties of rubber
[0092] Table 3 Rubber mechanical properties of Examples 1-3 and Comparative Examples 1-3
[0093] Tensile strength(MPa) Elongation at break (%) 100% modulus of tensile stress (MPa) Example 1 26.24 425 4.44 Example 2 27.94 439 4.75 Example 3 26.12 420 4.32 Comparative Example 1 21.71 376 3.37 Comparative Example 2 19.14 367 3.28 Comparative Example 3 26.12 428 3.87
[0094] It can be seen from Table 3 that compared with Comparative Examples 1-2, Examples 1-3 have improved mechanical properties, especially tensile strength; as the amount of lignin xanthate zinc vulcanization accelerator increases, the improvement effect becomes more obvious. Compared with the traditional vulcanization accelerator (DM), the present invention improves the mechanical properties of rubber, effectively improves the dispersibility of fillers in rubber, and improves the mechanical properties of rubber.
[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. Use of a lignin xanthate zinc vulcanization accelerator as shown in formula I in the preparation of rubber materials; I。 2. The use according to claim 1, characterized in that: The preparation method of the lignin zinc xanthate vulcanization accelerator comprises: reacting hydroxymethylated lignin with carbon disulfide, then adding a zinc-containing compound for flocculation, and obtaining a precipitate as the lignin zinc xanthate vulcanization accelerator.
3. The use according to claim 2, characterized in that: The method for preparing the hydroxymethylated lignin comprises adding an aldehyde compound into a liquid containing lignin substances for reaction.
4. The use according to claim 3, characterized in that: The pH of the liquid containing lignin substances is 10-14, and the concentration of lignin substances in the liquid containing lignin substances is 35-45 mg / mL; the aldehyde compounds include formaldehyde; and the mass ratio of the lignin substances to the aldehyde compounds is 5-7:
1.
5. The use according to claim 3, characterized in that: The preparation method of the hydroxymethylated lignin comprises heating a liquid containing lignin to 65-75° C. and adding an aldehyde compound to react.
6. The use according to claim 5, characterized in that: The reaction temperature is 65-75°C, and the reaction time is 3.5-4.5h.
7. The use according to claim 5, characterized in that: The reaction is carried out under stirring; the stirring rate is 200-400 rpm.
8. The use according to claim 2, characterized in that: The mass ratio of the hydroxymethylated lignin to carbon disulfide is 1:0.5-1.
5.
9. The use according to claim 2, characterized in that: The zinc-containing compound is any one or more combinations of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate.
10. The use according to claim 2, characterized in that: The zinc-containing compound is added in the form of a zinc-containing compound solution, the mass fraction of the zinc-containing compound solution is 10%-15%, and the molar volume ratio of the hydroxymethylated lignin to the zinc-containing compound solution is 1 mol: 6.3-10.3L.
11. The use according to claim 10, characterized in that: The molar volume ratio of the hydroxymethylated lignin to the zinc compound solution is 1 mol:7.3-9.3L.
12. The use according to claim 2, characterized in that The reaction temperature is 35-45°C, and the reaction time is 3.5-4.5h.
13. The use according to claim 1, characterized in that: The weight of the lignin zinc xanthate vulcanization accelerator is 5-10 parts per 100 parts of styrene-butadiene latex.
14. The use according to claim 1, characterized in that: The rubber material is made of the following components in parts by weight: 100 parts of styrene-butadiene latex, 40-50 parts of carbon black, 5-10 parts of lignin zinc xanthate vulcanization accelerator, 1-3 parts of stearic acid, 3-5 parts of zinc oxide, and 2-3 parts of vulcanizing agent; the solid content of the styrene-butadiene latex is 15%-25%.
Citation Information
Patent Citations
Vulcanization accelerator as well as preparation method and application thereof
CN113929608A
Preparation method of lignin xanthate
CN104448338A
Lignin zinc salt compound, preparation method, application, rubber composition and tire
CN115678038A